Clinical application of ultrasound in dermatological cases (Faculty of Medicine Universitas Indonesia, 2007)
Ultrasonography has been recognized as an important diagnostic modality in medicine and has entered the area of clinical dermatology. Its non-invasive characteristics have made it easily use and completely safe. It provides important diagnostic information in evaluating skin tumors. It also outlines the subcutaneous lesions and their relation to its adjacent tissue. Another ultrasound technique is color Doppler which is useful to assess vascularization of skin lesion. In this article, we would like to report ultrasound imaging in some selected cases from our institution. (Med J Indones 2007; 16:113-6)Keywords: Ultrasound, skin tumor, arteriovenous malformation, pseudoaneurysm